High-resolution absorption measurements of NH3 at high temperatures: 2100–5500 cm−1. (March 2017) - Barton, Emma J.; Yurchenko, Sergei N.; Tennyson, Jonathan; Clausen, Sønnik; Fateev, Alexander
Abstract: High-resolution absorption spectra of NH3 in the region 2100–5500 cm −1 at 1027 °C and approximately atmospheric pressure (1045±3 mbar) are measured. An NH3 concentration of 10% in volume fraction is used in the measurements. Spectra are recorded in a high-temperature gas-flow cell using a Fourier Transform Infrared (FTIR) spectrometer at a nominal resolution of 0.09 cm −1 . The spectra are analysed by comparison to a variational line list, BYTe, and experimental energy levels determined using the MARVEL procedure. 2308 lines have been assigned to 45 different bands, of which 1755 and 15 have been assigned or observed for the first time in this work. Abstract : Highlights: Absorption spectrum of ammonia recorded at 1300 K. 2038 line assignments, 1755 newly assigned. 15 bands observed for the first time.